2012
DOI: 10.1186/1478-7547-10-1
|View full text |Cite
|
Sign up to set email alerts
|

Methodologies used in cost-effectiveness models for evaluating treatments in major depressive disorder: a systematic review

Abstract: BackgroundDecision makers in many jurisdictions use cost-effectiveness estimates as an aid for selecting interventions with an appropriate balance between health benefits and costs. This systematic literature review aims to provide an overview of published cost-effectiveness models in major depressive disorder (MDD) with a focus on the methods employed. Key components of the identified models are discussed and any challenges in developing models are highlighted.MethodsA systematic literature search was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 69 publications
(259 reference statements)
2
31
0
Order By: Relevance
“…212,215,217 The most recent review, by Ali Afzali et al, 218 investigates 14 depression models from the literature and finds evidence of substantial heterogeneity in model structures and types, techniques employed, time horizons and data sources used. The authors identified two key potential problems arising in some of the models reviewed: first, a short time horizon for analysis, particularly where decision trees were employed, which limited the ability of the analysis to capture long-term effects of the interventions (e.g.…”
Section: Quantifying the Impact Of Multimorbidity In A Model-based Comentioning
confidence: 99%
See 2 more Smart Citations
“…212,215,217 The most recent review, by Ali Afzali et al, 218 investigates 14 depression models from the literature and finds evidence of substantial heterogeneity in model structures and types, techniques employed, time horizons and data sources used. The authors identified two key potential problems arising in some of the models reviewed: first, a short time horizon for analysis, particularly where decision trees were employed, which limited the ability of the analysis to capture long-term effects of the interventions (e.g.…”
Section: Quantifying the Impact Of Multimorbidity In A Model-based Comentioning
confidence: 99%
“…There are some published DES models relevant to depression, but none has included another condition. [211][212][213][214][215] The characteristics of depression alone, and particularly the characteristics of depression alongside another condition, make DES the ideal modelling approach to address the stated research question.…”
Section: Modelling Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…165 This may be why past economic evaluation modelling studies have focused on shorter time frames. 166 The target population for the economic model was Deaf BSL users with depression and/or anxiety. Originally, it was planned to analyse the diagnosis groups separately (e.g.…”
Section: Exploratory Economic Evaluation (Study 5)mentioning
confidence: 99%
“…Most of these assessments were recently compared in a well designed systematic review [7]. Multiple treatment meta-analysis reported that one of the selective serotonin reuptake inhibitors [SSRIs] escitalopram, was the most cost-eff ective therapy of depression in primary care settings among the other antidepressants tested [citalopram, duloxetine, fl uoxetine, fl uvoxamine mirtazapine, paroxetine, reboxetine, sertraline and venlafaxine] [8].…”
Section: Introductionmentioning
confidence: 99%